IRON TABLET REMINDER AGAINST HAEMOGLOBIN INCREASE ON PREGNANT WOMEN IN WARUREJA COMMUNITY HEALTH CENTER - Susi Setyaningsih; Ulfatul Latifah; Adevia Maulidya Chikmah (Siklus : Journal Research Midwifery Politeknik Tegal, 2020)
There were 326.3 million cellphone users in Indonesia and an increase of about 2% in 2016. One application most used by people was short text messenger (SMS), it also can be used as a reminder from health facility to their patients such as drinking iron tablet. Anemia, in Indonesia, still a significant cause of maternal mortality. This study aims to determine SMS's effect as a reminder of consuming iron tablets to increase hemoglobin on pregnancy. This study was a quantitative study with a Quasi Experiment using pre and post-test group design with a control group without randomization. Sample in this study taken using total sampling and obtained 31 respondents. Collected data analyzed using t-test analysis. The findingof this studystatistically shows ap-value 0,0001, which means thatiron tablets increasehemoglobin levels in pregnant women with anemia. It is expected that health workers could utilize technology to help to educate and monitoring pregnant women's behavior in consuming the iron tablet. Keyword: SMS reminder, iron tablets, Hemoglobin